DEACTIVATION OF HYDRODENITROGENATION CATALYST AND ITâ??S LIFETIME PREDICTION - , Triyono ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
The decrease of catalyst activity with time on stream during hydrodenitrogenation reaction was used to predict the lifetime of Pt/SiO2 catalyst. The catalyst investigated was Pt/SiO2 operated at several reaction temperatures. Loss of activity accompanied by loss of some importance catalyst properties such as surface area, acidity, pore volume, average pore radius and pore size distribution for fresh and spent catalysts were determined. Reaction were carried out in a differential reactor 25 cm long and 0.25 cm ID stainless steel tubing operated from 300 up to 380oC monitored by a thermocouple connected to an instrulab 2000 data logger. Catalyst activities presented in this paper was based on the butylamine conversion after reactions proceed for 15, 30, 45, 60 and 75 minutes at the regulated temperature. The results showed that the characters of fresh Pt/SiO2 catalyst were: acidity = 7.12 mmol/g